Enhanced lung volumes and pressures in traditional wind instrument musicians: The case of the Mejwez - Mohammad Z. Darabseh; Aseel Aburub; Ragad Alkaraki; Abdullah Saber Alshammari; Yazan Almansi; Ghaith Dalalah; Csaba Melczer; Pongrác Ács (PLoS ONE, 2026)
To evaluate pulmonary function and respiratory muscle strength in Mejwez players compared to predicted norms, and to assess the influence of smoking behaviours on these outcomes. A cross-sectional study was conducted involving adult Mejwez players. Spirometric parameters (forced expiratory volume in one second (FEV₁), forced vital capacity (FVC), and FEV₁/FVC) and respiratory pressures (maximal inspiratory pressure (MIP) and maximal expiratory pressure (MEP)) were measured and compared to predicted values. Multiple linear regression was used to assess the impact of smoking behaviours on respiratory outcomes. Mejwez players demonstrated significantly higher FEV₁ (+0.38 L, p < 0.001), FVC (+0.24 L, p = 0.001), MIP (+7.7 cm H₂O, p = 0.014), and MEP (+7.1 cm H₂O, p = 0.017) compared to predicted norms. Waterpipe smoking was significantly associated with reduced MIP (β = –9.3, p = 0.024) and MEP (β = –8.6, p = 0.025), while cigarette and vaping use showed no significant associations. This is the first study to characterise respiratory adaptations in Mejwez players, revealing enhanced pulmonary and respiratory muscle function. Waterpipe smoking was a significant negative predictor of respiratory strength. These findings highlight traditional music as a culturally relevant tool for respiratory health promotion and underscore the need for interventions addressing waterpipe use in the Middle East.